Neuroprotective Effect of Nosustrophine in a 3xTg Mouse Model of Alzheimer's Disease - Iván Carrera; Lola Corzo; Olaia Martínez-Iglesias; Vinogran Naidoo; Ramón Cacabelos (MDPI AG, 2023)
Neurodegeneration, characterized by the progressive deterioration of neurons and glial cells, is a feature of Alzheimer's disease (AD). The present study aims to demonstrate that the onset and early progression of neurodegenerative processes in transgenic mice models of AD can be delayed by a cocktail of neurotrophic factors and derived peptides named Nosustrophine, a nootropic supplement made by a peptide complex extracted from the young porcine brain, ensuring neuroprotection and improving neuro-functional recovery. Experimental 3xTg-APP/Bin1/COPS5 transgenic mice models of AD were treated with Nosustrophine at two different early ages, and their neuropathological hallmark and behavior response were analyzed. Results showed that Nosustrophine increased the activity of the immune system and reduced pathological changes in the hippocampus and cortex by halting the development of amyloid plaques, mainly seen in mice of 3-4 months of age, indicating that its effect is more preventive than therapeutic. Taken together, the results indicate the potent neuroprotective activity of Nosustrophine and its stimulating effects on neuronal plasticity. This study shows for the first time an effective therapy using nootropic supplements against degenerative diseases, although further investigation is needed to understand their molecular pathways.